Kaposi's sarcoma-associated herpesvirus seropositivity is associated with type 2 diabetes mellitus: A case–control study in Xinjiang, China. (March 2019) - Cui, Meng; Fang, Qiwen; Zheng, Jun; Shu, Zhanjun; Chen, Yin; Fan, Yage; Zhao, Juan; Wood, Charles; Zhang, Tiejun; Zeng, Yan
Highlights: Patients with type 2 diabetes mellitus have an elevated risk of Kaposi's sarcoma-associated herpesvirus (KSHV) infection. KSHV is more inclined to express both the latent and lytic antigens in diabetic patients. KSHV antibody titers and viral load are positively related and both increased with blood glucose levels in the KSHV-infected population. Abstract: Objective: To assess the potential relationship between Kaposi's sarcoma-associated herpesvirus (KSHV) infection and type 2 diabetes mellitus (DM-2) in Xinjiang, China. Methods: A case–control study of consecutively included DM-2 patients and normal controls was conducted among the Uygur and Han populations in Xinjiang Uygur Autonomous Region, China. Blood samples were collected and KSHV seroprevalence, antibody titers, and viral load were investigated. Logistic regression analysis and multiple linear regression analysis were applied to explore determinants of the main outcome measures. Results: A total of 324 patients with DM-2 and 376 normal controls were included. The seroprevalence of KSHV was 49.1% (95% confidence interval (CI) 43.6–54.5%) for diabetic patients and 23.7% (95% CI 19.4–28.0%) for the control group. After adjusting for variables of ethnicity, sex, body mass index, occupation, educational level, marital status, age, and smoking and alcohol consumption habits, the association between DM-2 and KSHV infection still existed (odds ratio (OR) 2.94, 95% CI 2.05–4.22), and the risk of KSHV infection increased with glucose concentration (OR 1.35, 95% CI 1.21–1.51). KSHV was more likely to express both the latent and lytic antigens in diabetic patients (latent: OR 3.27, 95% CI 2.25–4.75; lytic: OR 3.99, 95% CI 2.68–5.93). Antibody titers and viral load increased in patients with higher blood glucose levels ( p < 0.001). Conclusions: Patients with DM-2 have an elevated risk of KSHV infection. Both antibody titers and viral load increased with blood glucose levels.